Timing of Intravenous Immunoglobulin Treatment and Risk of Coronary Artery Abnormalities in Children with Kawasaki Disease - Aswine K. Bal; Deepa Prasad; Maria Angela Umali Pamintuan; Elizabeth Mammen-Prasad; Anna Petrova (Pediatrics and Neonatology)
Kawasaki disease (KD) is a type of febrile self-limiting systemic vasculitis, which affects the coronary arteries (CA) and may cause cardiac ischemia during childhood and adult life. Intravenous immunoglobulin (IVIG) has become the standard therapy for KD. However, it is still uncertain if CA outcome is associated with the timing of IVIG administration with reference to fever onset. Methods: The present study was designed to identify the risk for development and delay in resolution of CA abnormalities in association with IVIG administration within or after 10 days of KD onset. A retrospective analysis of clinical signs, laboratory data, and prospectively collected echocardiography (ECHO) results of 106 children hospitalized with KD was utilized. Results: IVIG was administered to 86 (81.1%) patients within 10 days, and 20 (18.9%) patients received the first dose of IVIG after 10 days of illness. Among 23 (21.6%) patients who were diagnosed with CA lesions, 18 had a CA abnormality at initial ECHO, whereas they appeared after IVIG therapy in five patients. The risk for CA lesions on initial ECHO was higher among the patients who were admitted after 10 days of disease onset [odds ratio (OR) = 5.3, 95% confidence interval (CI) = 1.7–15.9] but comparable with the post-IVIG treatment group (OR = 3.1, 95% CI = 0.48–19.8). The age <1 year and erythrocyte sedimentation rate (ESR) > 40 mm/hour were associated with non-resolution of CA lesions within 9 weeks of KD onset. Overall, 95.6% of children had resolution of CA abnormalities within 6 months of onset of KD symptoms. Conclusion: The results of this study suggest that although IVIG treatment within 10 days is important to minimize development of cardiac pathology, neither occurrence of CA lesions in IVIG-treated children nor the time frame for resolution of established CA abnormalities was associated with the timing of IVIG administration. Age <1 year and high ESR (>40 mm/hour) predict a delay in resolution of CA lesions among children with KD.